Flicker threshold and pattern VEP latency in ocular hypertension and glaucoma - Atkin, A; Bodis-Wollner, I; Podos, SM; Wolkstein, M; Mylin, L; Nitzberg, S (Investigative ophthalmology & visual science, 1983)
Latency of the pattern visual-evoked potential (PVEP) was measured in 24 ocular hypertensive (OHT) patients, eight open-angle glaucoma (OAG) patients, and 37 control subjects. The PVEP stimulus was a 2.3 cycle/degree sinusoidal grating, counterphase-modulated at 1 Hz. Field size was 9 degrees and mean luminance 1.7 log ft-lamberts. For 22 of the 32 patients, a psycholphysical measure of dynamic contrast sensitivity at 8 Hz (DRC) was obtained with a 4 degrees diameter stimulus, by determining the mean value for the contrast sensitivities to a homogeneous flickering field and to a 1.2 cycle/degree counterphase-flickering grating. Patient DRC values were compared with previously published control data from 21 subjects. Mean PVEP latencies of both the OHT and the OAG patients were greater than normal (P less than 0.001), with the OAG value larger than the OHT value (P less than 0.001). Mean DRCs were lower than normal (P less than 0.002) for both patient groups, with the OAG value lower than the OHT value (P less than 0.025). DRC correlated with PVEP latency for these patients (r = -0.66, P less than 0.001).